Effectiveness of Interprofessional Consultation-Based Interventions for Delirium: A Scoping Review. (March 2022) - Monaghan, Caitlin; Martin, Grace; Kerr, Jason; Peters, Mary-Lynn; Versloot, Judith
Background: Interprofessional geriatric consultation teams and multicomponent interventions are established models for delirium care. They are combined in interprofessional consultative delirium team interventions; however, insight into this novel approach is lacking. Objective: To describe the effectiveness and core components of consultation-based interventions for delirium. Method: Ovid MEDLINE, EMBASE, PsycINFO, CINAHL, and ProQuest. Data on core intervention components, outcomes, facilitators, and barriers were extracted. Results: 10 studies were included. Core intervention components were systematic delirium screening, ongoing consultation, implementation of non-pharmacologic and pharmacological interventions, and staff education. Of the included studies, 1/6 found a significant reduction in delirium incidence, 1/2 a reduction in delirium duration, and 2/3 found a reduction in falls. Facilitators and barriers to implementation were discussed. Conclusion: There was consistency in team structure and core components, however intervention operationalization and effectiveness varied widely. There is some evidence that this model is effective for reducing delirium and its sequelae.